1968
DOI: 10.1029/ja073i009p03005
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric winds over Yuma, Arizona, measured by gun-launched projectiles

Abstract: The newly installed 420‐mm smoothbore gun at Yuma Proving Ground, Arizona, is described with its associated ground instrumentation. With an improved ignition system, this gun has placed an 84‐kg projectile at an altitude of 180 km. Twenty‐four of these projectiles carrying liquid trimethyl aluminum have been used to measure ionospheric winds through the creation of luminous trails. Analysis of these trails shows the presence of quite large easterlies at 110 km and a general descent of the wind patterns through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
3
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
3
3
0
Order By: Relevance
“…Wavelengths of 24 km near 90 km, increasing with altitude to 40 km above 120 km, are in excellent agreement with those reported by Murphy and Bull [1968] for Yuma. They are considerably larger, particularly at lower altitudes, than those found by Kochanski [ 1964], which varied from about 12 km below 100 km to 16 km at 120 kin, 28-30 km at 130 kin, and an occasional 40-50 km above 140 km.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Wavelengths of 24 km near 90 km, increasing with altitude to 40 km above 120 km, are in excellent agreement with those reported by Murphy and Bull [1968] for Yuma. They are considerably larger, particularly at lower altitudes, than those found by Kochanski [ 1964], which varied from about 12 km below 100 km to 16 km at 120 kin, 28-30 km at 130 kin, and an occasional 40-50 km above 140 km.…”
supporting
confidence: 90%
“…Except for the upper part of the first (1954 HST) and the last (0225 HST) observations, a pronounced rotation with height is observable in these hodographs. Similar rotation has been reported by many investigators, although rotation is not observed in all trails, and, where it is noted, it is not always clockwise [Rosenberg and Edwards, 1964;Kochanski, 1964;Murphy, 1969;Bedinger et al, 1968;Murphy and Bull, 1968]. A study of 18 Kauai experiments conducted in May and June showed 12 experiments with clockwise rotation over a height interval of at least 20 km between 90 and 120 km.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…; 88,; 89,Murphy and Bull [1967a]; 90,Murphy and Bull [1967b]; 91,Murphy and Bull [1968a]; 92,Murphy and Bull [1968b]; 93, Murphy et al [1966a]; 94, Murphy et al [1966b]; 95, Murphy et al [1969]; 96, Nakamura and Kimura [1969]; 97, Nakamura et al [1972a]; 98, Nakamura et al [1972b]; 99, Nakamura et al [1981]; 100, Odom et al [1997]; 101, Rees [1972]; 102, Rees and Sandford [1974]; 103, Rees et al [1972b]; 104, Rees et al [1973]; 105, Rees et al [1976]; 106,Rees et al [1977]; 107,Rofe [1960]; 108,Rofe [1961]; 109,Roper and Edwards [1974]; 110, Roper and Edwards [1975]; 111,Rosenberg [1964]; 112,; 113,Rosenberg and Justus [1966]; 114, 115, Rosenberg et al [1973]; 116, Smith et al [1967]; 117, Smith et al [1970]; 118,Teitelbaum [1973]; 119,Trowbridge [1984]; 120,Wright and Fedor [1967]; 121, Zimmerman et al [1973]; 122, Zimmerman et al [1974].…”
mentioning
confidence: 99%